2004
DOI: 10.1002/anie.200460788
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of Singly Charged Peptide Ions by Photodissociation at λ=157 nm

Abstract: Bond-selective chemistry has been a goal of photochemists for decades, particularly since the development and proliferation of tunable laser light sources. Nevertheless, for relatively large molecules, this goal has been elusive. Rapid intramolecular vibrational relaxation appears to redistribute energy throughout large molecules on timescales faster than dissociation so that any selectivity that may be injected by an excitation process is lost. The fragmentation of peptide ions activated by blackbody radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
170
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(188 citation statements)
references
References 23 publications
15
170
1
1
Order By: Relevance
“…Photodissociation (PD) is an alternative method for generating radicals by electronic excitation of a suitable precursor [18]. Undesirable side reactions are avoided with PD due to the specificity of the excitation chemistry.…”
mentioning
confidence: 99%
“…Photodissociation (PD) is an alternative method for generating radicals by electronic excitation of a suitable precursor [18]. Undesirable side reactions are avoided with PD due to the specificity of the excitation chemistry.…”
mentioning
confidence: 99%
“…Melittin, kassinin, Lys [0]bradykinin, bradykinin, dynorphin-␤, GSK-␤ ␤ inhibitor, myosin kinase inhibitor, and mouse ANP [1][2][3][4][5][6][7][8][9][10][11] were purchased from American Peptide Company (Sunnyvale, CA). Polyalanine peptides were synthesized in-house using standard Fmoc coupling methodology.…”
Section: Methodsmentioning
confidence: 99%
“…It is demonstrated that a naphthyl based 18-crown-6 adduct is ideally suited for attaching to a variety peptides and fragmenting them following absorption of 266 nm light. [7][8][9][10][11]. Though none of these techniques is perfect, each has characteristic strengths and weaknesses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The fragmentation of peptides has been intensively inves-tigated in the past using various activation methods such as black-body radiation 11 , infrared multi-photon excitation 12 , ultraviolet 13 and vacuum ultraviolet 14 excitation, and collisions with gas-phase molecules or surfaces 15,16 . These measurements typically display cleavage of the weak peptide bond as a consequence of statistical fragmentation where the internal energy is randomized before dissociation occurs.…”
Section: Introductionmentioning
confidence: 99%